High erosion-oxidation performance of Fe-based Nb or V containing multi-component alloys with Co addition at 1173 K. (25th December 2015) - Kusumoto, Kenta; Shimizu, Kazumichi; Yaer, Xinba; Hara, Hiroya; Tamura, Kazuhiro; Kawai, Hideki
Abstract: High temperature erosion-oxidation behavior of Fe-based Nb or V containing multi-component alloys with Co addition is investigated at 1173 K. High temperature erosion tests and oxidation tests are conducted to determine both erosion and oxidation behaviors. Oxide scales are detected on the surfaces with 5V–10Nb and 5V–10Co showing superior erosion-oxidation resistance at 1173 K. The erosion rate is high in V-containing samples without Co due to the occurrence of vanadium oxide attack. Whilst, with increasing of Co content, the erosion rate is reduced, indicating the addition of Co is an effective counter-measure. In Nb-containing samples on the other hand, oxidation is successfully controlled by the formation of a composite oxide layer regardless of the presence of Co, thereby reducing the erosion losses. Graphical abstract: Highlights: Vanadium oxide attack deteriorates erosion resistance of samples without Co. Cobalt improves the oxidation resistance of V containing sample significantly. 5V–10Co show superior E–O resistance than samples without Co at 1173 K. Oxidation is controlled in Nb-containing samples by composite oxide layer. Composite oxide layer helps to reduce the erosion losses.